Lichen Biodiversity Index (LBI) as Bio-monitoring Tool for Air Pollution Assessment in Shah Alam, Selangor - Nurul Adibah Mokhtar, Hafiz-Afham Khaini, Azlan Abas, Harinder Rai Singh, Faezah Pardi, Nurul Aida Kamal Ikhsan, Hartini Mahiddin, Asmida Ismail (International Journal of Advanced Science and Technology, 2020)
Lichens, a symbiotic relationship of fungus and algae are suitable to serve as bio-indicator of air pollution due to their ability to absorb toxic materials into their thallus. This study aimed to assess the air pollution status in Shah Alam based on Lichen Biodiversity Index (LBI) which was used to determine the effect of phytotoxic gases released from motor vehicles on the diversity of lichen. A total of 52 sampling stations in central Shah Alam were studied where 12 stations showed high alteration of air, 9 stations showed moderate alteration of air, 18 stations showed low alteration of air but with low naturality, 12 stations showed moderate naturality of air and one station showed high naturality of air. Central Shah Alam is considered polluted since 40.38% of the study area showed condition above moderate pollution level (low alteration/low naturality) while only 25% showed condition below moderate pollution level. Regression analysis showed a strong negative linear relationship between LBI value and frequency of motor vehicles (R2 = 0.902) which denoted that air pollution caused by motor vehicles negatively affected the diversity of lichen. Thirteen species of lichen were recorded with Pyxine cocoes was identified as the most tolerant lichen while Parmotrema praesorediosum was identified as the most sensitive lichen in the study area.